Preparation method and application of macromolecular degradable master batch
By using components such as maleic anhydride modified cellulose, modified starch and modified polylactic acid with epoxy group-containing polymers, polymers modified, polymers, etc., the problem of insufficient performance of existing masterbatches in terms of plasticity and strength is solved, and the preparation of high-performance masterbatches is achieved.
Patent Information
- Application Number
- CN202510206504.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing degradable masterbatches have insufficient performance in terms of plasticity and strength, making it difficult to meet the needs of high-performance masterbatches.
The polymer degradable masterbatches are prepared by using components such as maleic anhydride modified cellulose, modified starch and polymer modified polylactic acid containing epoxy group.
It significantly improves the tensile strength, elastic modulus and comprehensive performance of the masterbatch, improves its plasticity and strength, and meets the needs of high-performance masterbatches.
Smart Images

Figure CN119684685A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a preparation method and application of a polymer degradable masterbatch. Background Art
[0002] In the production process of plastics, masterbatch (plastic masterbatch) plays a vital role. Masterbatch is a particle composed of raw plastic materials, excess chemical additives, carrier resins and dispersants. It is an important raw material in the production process of plastic products. By preparing masterbatch, manufacturers can more accurately control the composition and performance of plastic products to ensure that they meet specific requirements and standards. Therefore, the development of degradable masterbatch has become the key, which not only meets environmental protection needs and improves product competitiveness, but also promotes the development of related industries and creates more economic and social value.
[0003] At present, the development of degradable masterbatch has achieved remarkable results, but there are still some shortcomings, mainly in the following aspects: (1) The plasticity of plastic products is poor. For example, the patent application with publication number CN103834065A discloses a method for preparing cellulose-reinforced masterbatch. Cellulose is usually used as a reinforcing agent. The cellulose-reinforced masterbatch can improve the hardness and wear resistance of injection molded products, but the plasticity and flexibility of injection molded products are poor. (2) The strength of plastic products needs to be improved. For example, the Chinese patent with authorization announcement number CN111793337B discloses a degradable masterbatch based on polylactic acid. Although polylactic acid is degradable, the mechanical properties of polylactic acid are generally poor. For example, the patent application with publication number CN103910910A discloses a degradable masterbatch based on starch, but the mechanical properties of starch are generally poor, and the processability of starch still needs to be improved. Therefore, the current degradable masterbatch still faces many challenges in terms of plasticity and strength. In order to fill this technological gap, it is necessary to develop a new type of biodegradable masterbatch that also has good properties such as plasticity and strength to meet the needs of high-performance masterbatch. Summary of the invention
[0004] (1) Technical problems solved
[0005] The purpose of the present invention is to provide a preparation method and application of a polymer degradable masterbatch, so as to solve the problem that the current degradable masterbatch has insufficient performance in terms of plasticity and strength.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a polymer degradable masterbatch is as follows, comprising the following steps: S1. Raw material mixing: by weight, 20 to 40 parts of maleic anhydride modified cellulose, 120 to 250 parts of modified starch, 120 to 250 parts of epoxy group-containing polymer modified polylactic acid, 5 to 12 parts of high-density polyethylene powder, 3 to 7 parts of lubricant, 4 to 8 parts of plasticizer, 3 to 9 parts of titanium dioxide particles and 3 to 9 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the materials are conveyed to the extruder; S2. Extrusion granulation: Set the extruder extrusion rate to 150~350kg / h, the screw speed to 350~550rpm, the processing temperature to 200~250℃, and melt extrude the material; S3. Screening and packaging: The extruded material is pulled into strips, and after cooling to room temperature, it is air-dried, pelletized, vibrated and screened, dried, and then homogenized.
[0008] Preferably, the preparation method of the maleic anhydride modified cellulose is as follows: by weight, 10-25 parts of cellulose are added to 100-150 parts of N, N-dimethylformamide, stirred evenly, and then 40-100 parts of maleic anhydride are added, and then heated to 100-130° C. and stirred for 2-4 hours, and then 100-150 parts of anhydrous ethanol are added, and then stirred for 2-4 hours, and then filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
[0009] Preferably, the mass ratio of cellulose to maleic anhydride is 4:1.
[0010] Preferably, the cellulose preparation method is as follows: dried bamboo is crushed, and then bamboo powder of 20-80 mesh is screened; by weight, 50-100 parts of bamboo powder and 200-500 parts of 12% nitric acid solution are added to a reactor, and then heated to 80-120° C., stirred for 5-10 hours, filtered, and then the filter residue is washed with deionized water until the pH value no longer changes, and then the filter residue is added with 100-150 parts of 10% NaOH solution, and then continued to heat to 90-120° C., stirred for 2-4 hours, filtered to remove hemicellulose and lignin, and then the filter residue is washed with hot water until the pH value no longer changes, and finally vacuum dried to obtain cellulose.
[0011] Preferably, the cellulose has a diameter of 80-250 nm and a length greater than 2 μm.
[0012] The main purpose of using maleic anhydride modified cellulose in the present invention is to improve the mechanical properties and dispersibility of cellulose. Through the introduction of maleic anhydride modified cellulose, the combination between cellulose and the master batch matrix can be strengthened, and a stronger chemical bond can be formed, thereby improving the tensile strength and elastic modulus of the master batch. The maleic anhydride group reacts with the hydroxyl group in the polylactic acid in the master batch to form an ester bond, and this chemical combination strengthens the bonding strength between cellulose and the matrix, effectively suppressing stress concentration and crack propagation. At the same time, the introduction of maleic anhydride modified cellulose can also improve the dispersion state of cellulose in the master batch matrix, making it more evenly distributed in the matrix, which is conducive to improving the mechanical properties and comprehensive properties of the master batch. Through these reactions, the application of maleic anhydride modified cellulose in the present invention can significantly improve the mechanical properties and dispersibility of cellulose, thereby improving the comprehensive properties of the master batch.
[0013] Preferably, the preparation method of the modified starch is: by weight, 2 to 4 parts of dibenzoyl peroxide, 10 to 20 parts of glycerol and 50 to 120 parts of starch are added to a reaction container, then stirred at room temperature for 24 to 36 hours, then heated to 150 to 180° C., continued stirring for 3 to 6 hours, and cooled to obtain the modified starch.
[0014] Preferably, the mass ratio of dibenzoyl peroxide, glycerol and starch is 1:5:(25-30).
[0015] The present invention aims to improve the mechanical properties and processability of starch by modifying starch with benzoyl peroxide and glycerol. First, benzoyl peroxide as an oxidant reacts with the hydroxyl groups in the starch molecular chain, and the hydroxyl groups of the starch are converted into carbonyl and carboxyl groups during the oxidation process to form a cross-linked structure. This structure not only enhances the strength and toughness of starch, making it exhibit excellent tensile strength and impact resistance, but also reduces the molecular fluidity of starch, thereby reducing its melting point and melting temperature, thereby greatly improving its processability. Secondly, the hydrogen bonds formed between glycerol and starch molecules further strengthen the interaction between the molecular chains, effectively improving the gel properties and viscosity of starch. This property is crucial for the processing performance and molding ability of starch, making starch easier to plastically deform and mold. In addition, the modification of benzoyl peroxide and glycerol also brings about a significant improvement in the thermal stability and water resistance of starch. The stable cross-linked structure provided by benzoyl peroxide enhances the thermal stability of starch, allowing it to maintain excellent mechanical properties under high temperature conditions. Glycerol effectively improves the water resistance of starch and reduces its water absorption rate, thereby improving the stability and durability of starch. In summary, the modification of benzoyl peroxide and glycerol significantly improved the mechanical properties and processability of starch, providing a solid foundation for the wide application of starch in the fields of food industry, packaging materials, biomedical materials, etc.
[0016] The mass ratio of dibenzoyl peroxide, glycerol and starch is limited to 1:5:(25-30) in the present invention in order to achieve a good match between the modification effects of dibenzoyl peroxide and glycerol on starch, so as to achieve optimized material properties. By introducing dibenzoyl peroxide, a cross-linked structure can be formed in the starch molecular chain. This cross-linked structure can significantly improve the strength, toughness and impact resistance of starch. However, excessive dibenzoyl peroxide may lead to excessive cross-linking, thereby reducing the processability of starch. Glycerol, as a plasticizer, can adjust the fluidity and plasticity of starch, improve its processability and molding ability. By limiting the mass ratio of 1:5:(25-30), the optimal ratio between dibenzoyl peroxide, glycerol and starch can be ensured. In this way, dibenzoyl peroxide and starch can form a moderate cross-linked structure, and the addition of glycerol can provide sufficient plasticizing effect, thereby achieving good modification of starch. This good match can make the modified starch have higher mechanical properties and processability at the same time, making it more suitable for various application fields. Therefore, by limiting the mass ratio of dibenzoyl peroxide, glycerol and starch to 1:5:(25~30), a good match between dibenzoyl peroxide and glycerol-modified starch can be achieved, thereby optimizing the material properties of the modified starch.
[0017] Preferably, the preparation method of the epoxy group-containing polymer modified polylactic acid is as follows: 100 parts of polylactic acid are vacuum dried at 60-80° C. for 3-6 hours, and then the dried polylactic acid and 3-9 parts of the epoxy group-containing polymer are put into a mixer, stirred at 170-200° C. for 3-6 hours for melting and mixing, and the epoxy group-containing polymer is obtained after cooling.
[0018] Preferably, the preparation method of the epoxy group-containing polymer is as follows: by weight, 15 to 30 parts of boron trifluoride etherate and 40 to 75 parts of hyperbranched polyester are mixed evenly and heated to 60 to 80° C., and then 10 to 15 parts of epichlorohydrin are added dropwise thereto. After reacting for 2 to 4 hours, excess water, epichlorohydrin and small molecule by-products are removed under a low pressure of 10 to 50 Pa, and then 20 to 40 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 60 to 75° C. for 2 hours. After cooling, 300 to 500 mL of chloroform is added at room temperature, and after mixing evenly, the mixture is filtered and then vacuum dried to obtain the epoxy group-containing polymer.
[0019] Preferably, the mass fraction ratio of the epoxy group-containing polymer to the polylactic acid is (3-9):100.
[0020] Preferably, the preparation method of the hyperbranched polyester is as follows: by weight, 70 to 100 parts of polylactic acid and 15 to 30 parts of polybutylene succinate are melt-mixed at 180 to 200° C., reacted for 10 to 30 minutes to obtain a polymer, and then the polymer is vacuum dried at 60 to 80° C. for 4 to 6 hours to obtain a hyperbranched polyester.
[0021] The purpose of the present invention to modify polylactic acid with an epoxy group-containing polymer is to improve the toughness and strength of the polylactic acid material. Although polylactic acid is an environmentally friendly and degradable material, its molecular chain is rigid and has limited toughness. Chemical micro-crosslinking: The epoxy group in the epoxy group-containing polymer can react with the carboxyl group in the polylactic acid to form a chemical micro-crosslink. This crosslinking can increase the connectivity and crystallinity of the polylactic acid molecular chain and improve the strength and toughness of the material. Intermolecular hydrogen bonding: Intermolecular hydrogen bonding can be formed between the epoxy group-containing polymer and the polylactic acid. The hydroxyl group in the epoxy group-containing polymer forms a hydrogen bond with the carboxyl group in the polylactic acid, which increases the mutual adsorption and compatibility of the material, thereby improving the mechanical properties of the material. The combined effect of these two mechanisms enables the epoxy group-containing polymer and the polylactic acid to form a more solid structure, thereby enhancing the toughness and strength of the material. Through the combined effect of these two aspects, the mechanical properties of the polylactic acid are significantly improved.
[0022] Preferably, the lubricant is stearic acid or oleamide.
[0023] Preferably, the plasticizer is mannose or fructose.
[0024] The present invention also provides an application of a polymer degradable masterbatch in the preparation of agricultural mulch film or food preservative film.
[0025] (3) Beneficial technical effects The present invention uses maleic anhydride to modify cellulose, aiming to achieve the enhancement of cellulose mechanical properties and optimization of dispersibility. By introducing maleic anhydride, the binding force between cellulose and polylactic acid matrix is effectively strengthened, the tensile strength and elastic modulus are significantly improved, and the dispersion state of cellulose in polylactic acid is optimized, thereby comprehensively improving the comprehensive performance of masterbatch. In addition, the present invention also adopts the modification technology of benzoyl peroxide and glycerol for starch, thereby greatly improving the mechanical properties and processing convenience of starch, and significantly enhancing its thermal stability and water resistance.
[0026] Furthermore, the present invention innovatively uses epoxy group-containing polymers to modify polylactic acid, and through the synergistic effect of chemical micro-crosslinking and intermolecular hydrogen bonds, the toughness and strength of polylactic acid materials are greatly improved, and its mechanical properties are significantly improved. In addition, the present invention also cleverly incorporates a variety of functional additives. The addition of high-density polyethylene is intended to enhance the hardness and rigidity of the masterbatch, thereby improving its durability and mechanical strength. Stearic acid or oleamide lubricants can effectively reduce adhesion, improve fluidity, increase melting temperature, and prevent oxidative degradation. Mannose and fructose play the role of plasticizers and degradation aids in the masterbatch. They not only increase the softness and plasticity of the plastic, improve processing performance, but also give it a certain biodegradability. Titanium dioxide, as a whitening agent and ultraviolet absorber, not only improves the whiteness and optical properties of the material, but also effectively absorbs ultraviolet rays and reduces its damage to the material.
[0027] Finally, epoxidized soybean oil plays the role of both plasticizer and stabilizer in the masterbatch, which not only enhances the softness and plasticity of the material, but also improves its thermal stability and weather resistance. By reacting with free radicals in the material, epoxidized soybean oil can effectively inhibit oxidation reactions, thereby slowing down the aging of the material.
[0028] In summary, the present invention achieves comprehensive optimization and improvement of the performance of the masterbatch by comprehensively utilizing a variety of modification technologies and functional additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope morphology image of the maleic anhydride modified cellulose prepared in Example 1 of the present invention.
[0030] Figure 2 The infrared Fourier spectra of the cellulose and maleic anhydride modified cellulose prepared in Example 1 of the present invention are shown.
[0031] Figure 3 The infrared Fourier spectra of the starch and modified starch prepared in Example 1 of the present invention are shown.
[0032] Figure 4 The infrared Fourier spectra of the polylactic acid prepared in Example 1 of the present invention and the polylactic acid modified by the epoxy group-containing polymer are shown. DETAILED DESCRIPTION
[0033] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0034] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 below shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0035] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0036] Example 1 A method for preparing a polymer degradable masterbatch is as follows, comprising the following steps: S1. Raw material mixing: In parts by weight, 20 parts of maleic anhydride-modified cellulose, 120 parts of modified starch, 120 parts of epoxy-containing polymer-modified polylactic acid, 5 parts of high-density polyethylene powder, 3 parts of lubricant, 4 parts of plasticizer, 3 parts of titanium dioxide particles and 3 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the material is conveyed to the extruder; S2 extrusion granulation: set the extruder extrusion capacity of 150kg / h, the screw speed of 350rpm, the processing temperature of 200 ℃, the material is melt extruded; S3. Screening and packaging: The extruded material is pulled into strips, and after cooling to room temperature, it is air-dried, pelletized, vibrated and screened, dried, and then homogenized.
[0037] The preparation method of the maleic anhydride modified cellulose is as follows: by weight, 10 parts of cellulose are added to 10 parts of N, N-dimethylformamide, stirred evenly, and then 40 parts of maleic anhydride are added, and then heated to 100°C and stirred for 3 hours, and then 100 parts of anhydrous ethanol are added, and then stirred for 2 hours, and then filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
[0038] The above-mentioned cellulose preparation method is as follows: the dried bamboo is crushed, and then 20 mesh bamboo powder is screened; by weight, 50 parts of bamboo powder and 200 parts of 12% nitric acid solution are added to a reactor, and then heated to 80°C, kept warm and stirred for 5 hours, and then filtered and the filter residue is washed with deionized water until the pH no longer changes, and then the filter residue is added with 10 parts of 10% NaOH solution, and then continued to heat to 90°C, stirred for 2 hours, and then filtered to remove hemicellulose and lignin, and then the filter residue is washed with hot water until the pH no longer changes, and finally vacuum dried to obtain cellulose.
[0039] The above-mentioned cellulose has a diameter of 80 nm and a length of 3 μm.
[0040] The preparation method of the modified starch is as follows: by weight, 2 parts of dibenzoyl peroxide, 10 parts of glycerol and 50 parts of starch are added into a reaction container, and then stirred at room temperature for 24 hours, and then heated to 150° C., and continued to stir for 3 hours, and then cooled to obtain the modified starch.
[0041] The preparation method of the above-mentioned epoxy group-containing polymer modified polylactic acid is as follows: 100 parts of polylactic acid are vacuum dried at 60°C for 3 hours, and then the dried polylactic acid and epoxy group-containing polymer are put into a mixer, stirred at 170°C for 3 hours for melting and mixing, and the epoxy group-containing polymer is obtained after cooling.
[0042] The preparation method of the above-mentioned epoxy group-containing polymer is as follows: by weight, 15 parts of boron trifluoride etherate and 40 parts of hyperbranched polyester are mixed evenly and heated to 60°C, and then 10 parts of epichlorohydrin are added dropwise thereto. After the reaction is carried out for 3 hours, excess water, epichlorohydrin and small molecular by-products are removed under a low pressure of 10 Pa, and then 20 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 60°C for 2 hours. After cooling, 300 mL of chloroform is added at room temperature, and the mixture is evenly mixed and filtered, and then vacuum dried to obtain an epoxy group-containing polymer.
[0043] The preparation method of the above-mentioned hyperbranched polyester is as follows: by weight, 70 parts of polylactic acid and 15 parts of polybutylene succinate are melt-mixed at 180° C., reacted for 10 minutes to obtain a polymer, and then the polymer is vacuum-dried at 60° C. for 4 hours to obtain a hyperbranched polyester.
[0044] The lubricant is stearic acid; the plasticizer is manna.
[0045] Example 2
[0046] A method for preparing a polymer degradable masterbatch is as follows, comprising the following steps: S1. Raw material mixing: In parts by weight, 25 parts of maleic anhydride-modified cellulose, 150 parts of modified starch, 180 parts of epoxy-containing polymer-modified polylactic acid, 7 parts of high-density polyethylene powder, 4 parts of lubricant, 5 parts of plasticizer, 6 parts of titanium dioxide particles and 5 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the material is conveyed to the extruder; S2 extrusion granulation: set the extruder extrusion capacity of 200kg / h, the screw speed of 400rpm, the processing temperature of 210 ℃, the material is melt extruded; S3. Screening and packaging: The extruded material is pulled into strips, and after cooling to room temperature, it is air-dried, pelletized, vibrated and screened, dried, and then homogenized.
[0047] The preparation method of the maleic anhydride modified cellulose is as follows: by weight, 15 parts of cellulose are added to 120 parts of N, N-dimethylformamide, stirred evenly, and then 60 parts of maleic anhydride are added, and then heated to 110° C. and stirred for 3 hours, and then 120 parts of anhydrous ethanol are added, and then stirred for 3 hours, and then filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
[0048] The above-mentioned cellulose preparation method is as follows: dried bamboo is crushed, and then 40-mesh bamboo powder is screened; by weight, 70 parts of bamboo powder and 300 parts of 12% nitric acid solution are added to a reactor, and then heated to 90°C, kept warm and stirred for 6 hours, and then filtered and the filter residue is washed with deionized water until the pH no longer changes, and then the filter residue is added with 120 parts of 10% NaOH solution, and then continued to heat to 100°C, stirred for 3 hours, and then filtered to remove hemicellulose and lignin, and then the filter residue is washed with hot water until the pH no longer changes, and finally vacuum dried to obtain cellulose.
[0049] The above-mentioned cellulose has a diameter of 120 nm and a length of 4 μm.
[0050] The preparation method of the modified starch is as follows: by weight, 3 parts of dibenzoyl peroxide, 15 parts of glycerol and 80 parts of starch are added to a reaction container, then stirred at room temperature for 28 hours, then heated to 160° C., continued to stir for 4 hours, and cooled to obtain the modified starch.
[0051] The preparation method of the epoxy group-containing polymer modified polylactic acid is as follows: 100 parts of polylactic acid are vacuum dried at 70° C. for 4 hours by weight. Then the dried polylactic acid and the epoxy group-containing polymer are put into a mixer, stirred at 180° C. for 4 hours for melting and mixing, and cooled to obtain the epoxy group-containing polymer.
[0052] The preparation method of the above-mentioned epoxy group-containing polymer is as follows: in parts by weight, 20 parts of boron trifluoride etherate and 55 parts of hyperbranched polyester are mixed evenly and heated to 70°C, and then 12 parts of epichlorohydrin are added dropwise thereto. After the reaction is carried out for 3 hours, excess water, epichlorohydrin and small molecular by-products are removed under a low pressure of 20 Pa, and then 25 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 65°C for 2 hours. After cooling, 350 mL of chloroform is added at room temperature, and the mixture is evenly mixed and filtered, and then vacuum dried to obtain the epoxy group-containing polymer.
[0053] The preparation method of the above-mentioned hyperbranched polyester is as follows: 80 parts of polylactic acid and 18 parts of polybutylene succinate are melt-mixed at 190° C. by weight, reacted for 20 minutes to obtain a polymer, and then the polymer is vacuum dried at 70° C. for 5 hours to obtain a hyperbranched polyester.
[0054] The lubricant is stearic acid; the plasticizer is fructose.
[0055] Example 3
[0056] A method for preparing a polymer degradable masterbatch is as follows, comprising the following steps: S1. Raw material mixing: In parts by weight, 35 parts of maleic anhydride-modified cellulose, 220 parts of modified starch, 210 parts of epoxy-containing polymer-modified polylactic acid, 10 parts of high-density polyethylene powder, 6 parts of lubricant, 7 parts of plasticizer, 8 parts of titanium dioxide particles and 8 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the material is conveyed to the extruder; S2 extrusion granulation: set the extruder extrusion capacity of 300kg / h, the screw speed of 500rpm, the processing temperature of 230 ℃, the material is melt extruded; S3. Screening and packaging: The extruded material is pulled into strips, and after cooling to room temperature, it is air-dried, pelletized, vibrated and screened, dried, and then homogenized.
[0057] The preparation method of the maleic anhydride modified cellulose is as follows: by weight, 20 parts of cellulose are added to 135 parts of N, N-dimethylformamide, stirred evenly, and then 80 parts of maleic anhydride are added, and then heated to 120°C and stirred for 3 hours, and then 140 parts of anhydrous ethanol are added, and then stirred for 3 hours, and then filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
[0058] The above-mentioned cellulose preparation method is as follows: dried bamboo is crushed, and then 60-mesh bamboo powder is screened; 90 parts of bamboo powder and 400 parts of 12% nitric acid solution are added to a reactor by weight, and then heated to 110°C, kept warm and stirred for 8 hours, and then filtered and the filter residue is washed with deionized water until the pH no longer changes, and then the filter residue is added with 140 parts of 10% NaOH solution, and then continued to heat to 110°C, stirred for 3 hours, and then filtered to remove hemicellulose and lignin, and then the filter residue is washed with hot water until the pH no longer changes, and finally vacuum dried to obtain cellulose.
[0059] The above-mentioned cellulose has a diameter of 220 nm and a length of 8 μm.
[0060] The preparation method of the modified starch is as follows: by weight, 3 parts of dibenzoyl peroxide, 15 parts of glycerol and 90 parts of starch are added to a reaction container, then stirred at room temperature for 32 hours, then heated to 170° C., continued to stir for 5 hours, and cooled to obtain the modified starch.
[0061] The preparation method of the epoxy group-containing polymer modified polylactic acid is as follows: 100 parts of polylactic acid are vacuum dried at 70° C. for 5 hours, and then the dried polylactic acid and 8 parts of the epoxy group-containing polymer are put into a mixer, stirred at 190° C. for 5 hours for melting and mixing, and cooled to obtain the epoxy group-containing polymer.
[0062] The preparation method of the above-mentioned epoxy group-containing polymer is as follows: by weight, 25 parts of boron trifluoride etherate and 65 parts of hyperbranched polyester are mixed evenly and heated to 70°C, and then 12 parts of epichlorohydrin are added dropwise thereto. After the reaction is carried out for 3 hours, excess water, epichlorohydrin and small molecular by-products are removed under a low pressure of 40 Pa, and then 35 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 70°C for 2 hours. After cooling, 400 mL of chloroform is added at room temperature, and the mixture is evenly mixed, filtered, and then vacuum dried to obtain the epoxy group-containing polymer.
[0063] The preparation method of the above-mentioned hyperbranched polyester is as follows: 90 parts of polylactic acid and 25 parts of polybutylene succinate are melt-mixed at 190° C. by weight, reacted for 20 minutes to obtain a polymer, and then the polymer is vacuum dried at 70° C. for 5 hours to obtain a hyperbranched polyester.
[0064] The lubricant is stearic acid; the plasticizer is fructose.
[0065] Example 4
[0066] A method for preparing a polymer degradable masterbatch is as follows, comprising the following steps: S1. Raw material mixing: In parts by weight, 40 parts of maleic anhydride-modified cellulose, 250 parts of modified starch, 250 parts of epoxy group-containing polymer-modified polylactic acid, 12 parts of high-density polyethylene powder, 7 parts of lubricant, 8 parts of plasticizer, 9 parts of titanium dioxide particles and 9 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the material is conveyed to the extruder; S2 extrusion granulation: set the extruder extrusion capacity of 350kg / h, the screw speed of 550rpm, the processing temperature of 250 ℃, the material is melt extruded; S3. Screening and packaging: The extruded material is pulled into strips, and after cooling to room temperature, it is air-dried, pelletized, vibrated and screened, dried, and then homogenized.
[0067] The preparation method of the maleic anhydride modified cellulose is as follows: by weight, 25 parts of cellulose are added to 150 parts of N, N-dimethylformamide, stirred evenly, and then 100 parts of maleic anhydride are added, and then heated to 130° C. and stirred for 4 hours, and then 150 parts of anhydrous ethanol are added, and then stirred for 4 hours, and then filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
[0068] The above-mentioned cellulose preparation method is as follows: dried bamboo is crushed, and then 80-mesh bamboo powder is screened; by weight, 100 parts of bamboo powder and 500 parts of 12% nitric acid solution are added to a reactor, and then heated to 120°C, kept warm and stirred for 10 hours, and then filtered and the filter residue is washed with deionized water until the pH no longer changes, and then the filter residue is added with 150 parts of 10% NaOH solution, and then continued to heat to 120°C, stirred for 4 hours, and then filtered to remove hemicellulose and lignin, and then the filter residue is washed with hot water until the pH no longer changes, and finally vacuum dried to obtain cellulose.
[0069] The above-mentioned cellulose has a diameter of 250 nm and a length of 10 μm.
[0070] The preparation method of the modified starch is as follows: by weight, 4 parts of dibenzoyl peroxide, 20 parts of glycerol and 120 parts of starch are added to a reaction container, then stirred at room temperature for 36 hours, then heated to 180° C., continued to stir for 6 hours, and cooled to obtain the modified starch.
[0071] The preparation method of the epoxy group-containing polymer modified polylactic acid is as follows: 100 parts of polylactic acid are vacuum dried at 80° C. for 6 hours, and then the dried polylactic acid and 9 parts of the epoxy group-containing polymer are put into a mixer, stirred at 200° C. for 6 hours for melting and mixing, and cooled to obtain the epoxy group-containing polymer.
[0072] The preparation method of the above-mentioned epoxy group-containing polymer is as follows: by weight, 30 parts of boron trifluoride etherate and 75 parts of hyperbranched polyester are mixed evenly and heated to 80°C, and then 15 parts of epichlorohydrin are added dropwise thereto. After the reaction is carried out for 4 hours, excess water, epichlorohydrin and small molecular by-products are removed under a low pressure of 50 Pa, and then 40 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 75°C for 2 hours. After cooling, 500 mL of chloroform is added at room temperature, the mixture is mixed evenly, filtered, and then vacuum dried to obtain the epoxy group-containing polymer.
[0073] The preparation method of the above-mentioned hyperbranched polyester is as follows: by weight, 100 parts of polylactic acid and 30 parts of polybutylene succinate are melt-mixed at 200° C., reacted for 30 minutes to obtain a polymer, and then the polymer is vacuum-dried at 80° C. for 6 hours to obtain a hyperbranched polyester.
[0074] The lubricant is oleamide; the plasticizer is fructose.
[0075] Example 5
[0076] The method is basically the same as Example 1, except that the amount of maleic anhydride-modified cellulose used to prepare the masterbatch is 40 parts.
[0077] Comparative Example 1 The method is basically the same as Example 1, except that the cellulose used to prepare the masterbatch has not been modified with maleic anhydride.
[0078] Comparative Example 2 The method is basically the same as Example 1, except that the polylactic acid used to prepare the masterbatch has not been modified with the epoxy group-containing polymer.
[0079] Comparative Example 3 The method is basically the same as Example 1, except that the starch used to prepare the masterbatch has not been modified by dibenzoyl oxide and glycerol.
[0080] Comparative Example 4 The method is basically the same as Example 1, except that maleic anhydride-modified cellulose is not added in the preparation of the masterbatch.
[0081] Characterization Tests: The cellulose, maleic anhydride modified cellulose, modified starch, epoxy group-containing polymer, and modified polylactic acid in the masterbatch were analyzed by Fourier transform infrared spectroscopy (FTIR) in attenuated total reflectance (ATR) mode. All spectra were recorded in the range of 4000 to 400 cm -1 , the spectral resolution is 4 cm -1 , the number of scans is 32 times.
[0082] Figure 1 The scanning electron microscope morphology of the maleic anhydride modified cellulose prepared in Example 1 of the present invention shows that the maleic anhydride modified cellulose is evenly dispersed, which lays a solid foundation for the reinforcement masterbatch.
[0083] Figure 2 The infrared Fourier spectrum of the cellulose and maleic anhydride modified cellulose prepared in Example 1 of the present invention shows characteristic cellulose structure peaks, such as the vibration peak of CO (1050-1150 cm -1 ) and the vibration peaks of CH (2850–2970 cm -1In addition, the CH angle vibration peaks (1370–1470 cm -1 ) and the vibration peaks of OH (3200-3600 cm -1 ), the infrared spectrum of maleic anhydride-modified cellulose nanocrystals showed additional peaks, including the vibration peak of C=O (1700-1750 cm -1 ) and the vibration peaks of C=C (1600-1680 cm -1 ), further analysis revealed that chemical bonding was formed between maleic anhydride-modified cellulose nanocrystals and the polylactic acid in the masterbatch. Typical chemical bonding peaks included the vibration peaks of ester bonds (1720-1760 cm -1 ), these results indicate that maleic anhydride was successfully introduced and formed a chemical connection with polylactic acid, which provides an important basis for further studying the properties of maleic anhydride-modified cellulose nanocrystals.
[0084] Figure 3 Infrared Fourier spectrum of starch and modified starch prepared in Example 1 of the present invention, the hydroxyl region of starch usually shows a broad peak with a wave number range of 3600-3200 cm -1 , corresponding to OH stretching vibration. In addition, 1155 cm -1 and 1080cm -1 The peak at 982 cm corresponds to the stretching vibration of COC and C-OH in starch molecules, and the peak at 982 cm -1 The absorption peak at 1700-1750 cm corresponds to the CH bending vibration on the starch sugar ring. These characteristic absorption peaks reflect the molecular structure and vibration characteristics of the chemical bonds of starch in its original state. After starch is oxidized by dibenzoyl peroxide, the hydroxyl groups will be partially converted into carbonyl groups (C=O) and carboxyl groups (-COOH). Accordingly, the FTIR spectrum will show the following changes: 1700-1750 cm -1 A new absorption peak of carboxyl (-COOH) appears in the range of 2800-3000 cm -1 A new broad peak appears in the range.
[0085] Figure 4 The infrared Fourier spectrum of the polylactic acid and the polylactic acid modified with the epoxy group-containing polymer prepared in Example 1 of the present invention, the Fourier transform infrared spectroscopy (FTIR) analysis results of the polylactic acid and the polylactic acid modified with the epoxy group-containing polymer, in the range of 1000-1500 cm -1 In the spectral range, characteristic absorption peaks of CC skeleton vibration, C=O stretching vibration and CH plane bending vibration can be observed. When polylactic acid is modified with epoxy group-containing polymer, the peak area in this region is significantly reduced, and the peaks at 845 and 908 cm -1No obvious characteristic peak of epoxy group was detected at 1726 cm -1 The bands near the spectral band reflect the stretching vibration of the carbonyl group in polylactic acid. After adding the epoxy group-containing polymer, the spectral bands at 1600-1800 cm -1 A new absorption peak gradually appeared in the range, which was located at 1633 cm -1 At 3439 cm, it corresponds to the carbonyl absorption band caused by the hydrogen bond between the epoxy group-containing polymer and polylactic acid. At the same time, the hydroxyl stretching vibration absorption band of polylactic acid appears at 3439 cm -1 nearby.
[0086] Performance Test: Mechanical properties: According to the national standard "Determination of Tensile Properties of Plastics" (GB\T1040.3-2006) Part 3, the masterbatch is co-extruded blow molded or co-extruded into a film, and then the tensile strength and elongation at break are tested: the sample shape is dumbbell-shaped, with a length of 150mm and a width of 10mm, and is stretched at a speed of 200mm / min at room temperature 25℃.
[0087] Aging test: The aging test tests the mechanical properties after thermal aging. The thermal aging condition is aging at 60℃ for 1080h.
[0088] The properties of the plastics prepared from the masterbatches of Examples 1 to 5 and Comparative Examples 1 to 4 are summarized in Table 2.
[0089] Table 2 Properties of plastics prepared from masterbatches of Examples 1 to 5 and Comparative Examples 1 to 4
[0090] The main difference between Example 1 and Comparative Example 1 is whether the cellulose is modified by maleic anhydride. It can be clearly seen from Table 2 that maleic anhydride-modified cellulose can significantly improve the mechanical properties of the plastic prepared from the masterbatch.
[0091] The main difference between Example 1 and Comparative Example 2 is whether the polylactic acid is modified with a polymer containing epoxy groups. It can be clearly seen from Table 2 that the polylactic acid modified with a polymer containing epoxy groups can significantly improve the mechanical properties of the plastic prepared from the masterbatch.
[0092] The main difference between Example 1 and Comparative Example 3 is whether the starch is modified with dibenzoyl oxide and glycerol. It can be clearly seen from Table 2 that the starch modified with dibenzoyl oxide and glycerol can significantly improve the mechanical properties of the plastic prepared from the masterbatch.
[0093] The main difference between Example 1 and Comparative Example 4 is whether maleic anhydride-modified cellulose is added. It can be clearly seen that the addition of maleic anhydride-modified cellulose can significantly improve the mechanical properties of the plastic prepared from the masterbatch.
[0094] In summary, the maleic anhydride modified cellulose, modified starch, epoxy group-containing polymer, modified polylactic acid and other components in the present invention achieve a synergistic effect, can significantly improve the comprehensive performance of the masterbatch, and can provide excellent performance and effects in multiple fields.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a polymer degradable masterbatch, comprising the following steps: S1. Raw material mixing: by weight, 20 to 40 parts of maleic anhydride modified cellulose, 120 to 250 parts of modified starch, 120 to 250 parts of epoxy group-containing polymer modified polylactic acid, 5 to 12 parts of high-density polyethylene powder, 3 to 7 parts of lubricant, 4 to 8 parts of plasticizer, 3 to 9 parts of titanium dioxide particles and 3 to 9 parts of epoxidized soybean oil are mixed in a high-speed mixer, and then the materials are conveyed to the extruder; S2. Extrusion granulation: Set the extruder extrusion rate to 150~350kg / h, the screw speed to 350~550rpm, the processing temperature to 200~250℃, and melt extrude the material; S3. Screening and packaging: The extruded material is pulled into strips, cooled to room temperature, air-dried, pelletized, vibrated and screened, dried, and then homogenized; The preparation method of the epoxy group-containing polymer modified polylactic acid is as follows: 100 parts by weight of polylactic acid are vacuum dried at 60-80° C. for 3-6 hours, then the dried polylactic acid and 3-9 parts of the epoxy group-containing polymer are put into a mixer, stirred at 170-200° C. for 3-6 hours for melting and mixing, and cooled to obtain the epoxy group-containing polymer; The preparation method of the modified starch is as follows: by weight, 2-4 parts of dibenzoyl peroxide, 10-20 parts of glycerol and 50-120 parts of starch are added into a reaction container, then stirred at room temperature for 24-36 hours, heated to 150-180° C., stirred for 3-6 hours, and cooled to obtain the modified starch.
2. The method for preparing a polymer degradable masterbatch according to claim 1, characterized in that: The preparation method of maleic anhydride modified cellulose is as follows: by weight, 10-25 parts of cellulose are added to 100-150 parts of N, N-dimethylformamide, and then 40-100 parts of maleic anhydride are added after stirring evenly, and then the mixture is heated to 100-130° C. and stirred for 2-4 hours, 100-150 parts of anhydrous ethanol are added, and stirred for 2-4 hours, and then the residue is filtered and washed three times with anhydrous ethanol to remove unreacted maleic anhydride and N, N-dimethylformamide solvent, and finally dried to obtain maleic anhydride modified cellulose.
3. The method for preparing a polymer degradable masterbatch according to claim 2, characterized in that: The cellulose preparation method comprises the following steps: crushing dried bamboo, and then screening bamboo powder with a mesh size of 20 to 80; adding 50 to 100 parts of bamboo powder and 200 to 500 parts of nitric acid solution with a mass fraction of 12% by weight into a reaction kettle, heating to 80 to 120° C., stirring at the temperature for 5 to 10 hours, filtering, washing the filter residue with deionized water until the pH value no longer changes, adding 100 to 150 parts of NaOH solution with a mass fraction of 10%, and then continuing to heat to 90 to 120° C., stirring for 2 to 4 hours, filtering to remove hemicellulose and lignin, and then washing the filter residue with hot water until the pH value no longer changes, and finally vacuum drying to obtain cellulose; The cellulose has a diameter of 80-250 nm and a length greater than 2 μm.
4. The method for preparing a polymer degradable masterbatch according to claim 1, characterized in that: The mass ratio of the dibenzoyl peroxide, glycerol and starch is 1:5:(25-30).
5. The method for preparing a polymer degradable masterbatch according to claim 1, characterized in that: The preparation method of the epoxy group-containing polymer is as follows: by weight, 15 to 30 parts of boron trifluoride etherate and 40 to 75 parts of hyperbranched polyester are mixed evenly and heated to 60 to 80° C., and then 10 to 15 parts of epichlorohydrin are added dropwise thereto, and after reacting for 2 to 4 hours, excess water, epichlorohydrin and small molecular by-products are extracted under a low pressure of 10 to 50 Pa, and then 20 to 40 parts of saturated sodium hydroxide solution are added, and the reaction is continued at 60 to 75° C. for 2 hours, and after cooling, 300 to 500 mL of chloroform is added at room temperature, and after mixing evenly, the mixture is filtered, and then vacuum dried to obtain the epoxy group-containing polymer.
6. The method for preparing a polymer degradable masterbatch according to claim 5, characterized in that: The preparation method of the hyperbranched polyester is as follows: by weight, 70-100 parts of polylactic acid and 15-30 parts of polybutylene succinate are melt-mixed at 180-200° C., reacted for 10-30 minutes to obtain a polymer, and then the polymer is vacuum dried at 60-80° C. for 4-6 hours to obtain a hyperbranched polyester.
7. The method for preparing a polymer degradable masterbatch according to claim 1, characterized in that: The lubricant is stearic acid or oleamide; The plasticizer is mannose or fructose.
8. Use of a polymer degradable masterbatch obtained by the preparation method according to any one of claims 1 to 7 in the preparation of agricultural mulch film or food cling film.
Citation Information
Patent Citations
Plastic master batch
CN103834065A
Starch-containing master batches
CN103910910A
An antibacterial polylactic acid masterbatch and its application
CN111793337B
Polylactic acid / starch full bio-based degradable composite material and preparing method thereof
CN102604349A
Full-bio-based toughened polylactic acid composite and preparation method thereof
CN108587095A
Cited By
Chinese herbal medicine component for relieving neurodegenerative diseases and preparation method thereof
CN120899655A